PENDIDIKAN KARAKTER: UPAYA MEMBENTUK GENERASI BERKESADARAN MORAL - Much. Arif Saiful Anam (UIN Sunan Ampel Surabaya, 2014)
The post-reform moral crisis shows that the achievement of moral competence processed at school has not been able to result the optimal output to the moral awareness generation development of nation. This condition such that begun from verbalistic growth culture from the learning process which inclines to only teach moral education as the textual limitation. That phenomenon and fact cause many sides conclude that the importance of character education implementation intensively as the essence of moral awareness generation development. This perspective places moral as the main environment aspect which decides generation characterization. Therefore, moral awareness should be learned intently and progressed or developed by character education applicatively. When the first time of implementation of character education in the school environment, it needs to do by the moral conditioning then continue to the moral training. The Design Character education like this has a function as systemic moral ideas in progressing the generation moral awareness which is able to supply young generation with moral intelligence competence and character.